MODEL DEVELOPMENT OF THE RELATIONSHIP OF VISUAL ATTENTION ON NATURAL SKIN CARE PRODUCT PACKAGING AND PURCHASE INTENTION BASED ON NEUROMARKETING STUDY - Listia Chaerani, Metha
Significant growth in the beauty and skincare sector, particularly in natural skincare products, is driven by the high trend in adopting a healthy lifestyle and using environmentally friendly products. This phenomenon also triggers high competition for companies in sector. Various methods are employed by companies to make their products competitive and stand out in the market. One of the approaches is through product packaging marketing. Product packaging is considered as an effective communication tool between consumers and the products. The proper selection of packaging design for a product becomes a tool for communicating brand identity, attracting consumer attention, and assisting in placing the product in a specific category. Furthermore, packaging plays a crucial role in adding value to the product and influencing consumer purchase behavior. The appealing design elements on packaging are the key to success in capturing consumers' attention towards the product. These features can be considered through two aspects, namely visual and textual attributes. Visual attributes, such as the shape of the packaging, layout and material texture, are considered capable of capturing attention and transmitting non-verbal information that can trigger emotions in consumers. On the other hand, textual attributes typically convey verbal and numeric information that influences consumer cognition. In products containing natural ingredients, textual attributes can be associated with the presence of an eco-label. There are many methods that can be used to study packaging design features that can attract consumer attention and influence purchase behavior. A method that has gained attention in the field of marketing is neuromarketing. This method is considered more effective because it contains cognitive science and neuroscience in marketing research. Therefore, this research involves the design of natural skincare product packaging using neuromarketing eye-tracker and EEG techniques, which can capture visual attention and influence consumer purchase intention through emotional variables and visual-haptic perception. In addition, this study will also test different types of design elements, including shape, texture, layout, and eco-label. The method used in this research is an experiment using eye-tracker and EEG to measure visual attention of packaging design features of natural skincare products. Additionally, ANOVA and regression method are used to examine the relationships between variables in this study. Data collection was carried out at the laboratory of business system innovation and development (LIPSP), faculty of industrial technology, Bandung Institute of Technology, involving 43 respondents. There are sixteen stimuli representing variations in the packaging design of natural skincare products presented to the respondents. The stimulus presentation method used is within-subjects, and the sequence of stimulus presentation used is the partial counterbalancing method. The research results indicate that texture and eco-label factors exhibit a significant difference in participants' visual attention. On the other hand, there is no significant difference in participants' visual attention for each type of shape and layout in product packaging design. Based on the Heatmaps analysis, it is known that general information on the label, including brand, benefits, function, content, product volume, and eco-label arranged in both symmetric and asymmetric layouts, is capable to attract participants' attention to read or pay attention to the displayed information on the product. The results of EGG analysis that is represented through beta and gamma waves, show differences in emotional responses when different stimuli are presented. Spearman Rank correlation results show that there is a positive correlation between visual attention to designs with glossy on EEG indicators. The evaluation results of the research model tested using regression techniques indicate a significant influence between packaging features and purchase intention mediated by visual-haptic perception and emotion variables. The result of this research using the combination of neuromarketing and questionnaire shows that packaging features mediated by visual-haptic perception and emotion variables have significant effect on purchase intention.